Three new species of Demidospermus (Monopisthocotyla: Dactylogyridae) parasitizing Ageneiosus inermis (Siluriformes: Auchenipteridae) from western Amazon, Brazil - Justo, Marcia Cristina Nascimento; Martins, Williane Maria De Oliveira; Cohen, Simone Chinicz (Zootaxa, 2024)
During a study on the helminth fauna of fishes in the Juruá and Moa Rivers, State of Acre, north Brazil, three new species of Demidospermus Suriano, 1983 were found parasitizing Ageneiosus inermis (Auchenipteridae). Demidospermus juruaensis sp. nov. is characterized by its accessory piece, which is robust and straight, anchor-shaped distally, as well as by morphology of its hooks, which have a delicate and expanded shaft with a spear-shape ending. Demidospermus bifurcatus sp. nov. is characterized by a male copulatory organ (MCO) composed of a robust tube, with a bisected tip at the distal end and a robust accessory piece, that embraces the MCO along its entire length. Demidospermus takemotoi sp. nov. differs from its congeners by its long, tubular and slender accessory piece, which is almost the same length as the MCO. These findings bring the number of valid Demidospermus species to 36. The results of this research on the helminth parasites of fishes in Acre State underscore the importance of carrying similar studies on other fish species, thereby enhancing understanding of biodiversity in the Neotropical Region.